Local structural distortion and interrelated phonon mode studies in yttrium chromite. Issue 8 (30th January 2017) - Mannepalli, Venkateswara Rao; Raghunathan, Rajamani; Ramadurai, Ranjith; David, Adrian; Prellier, Wilfrid
Abstract: Abstract : YCrO3 (YCO) perovskite has been originally reported to be a biferroic with antiferromagnetic and ferroelectric (FE) properties, in which the origin of FE in YCO remains ambiguous. However, further studies reveal the presence of a global orthorhombic Pnma structure with a local structural heterogeneity. In this study, we discuss the high temperature phonon modes and their inter-relation to local structural distortions in YCO perovskite through Raman spectroscopy experiments and density functional theory (DFT) calculations. We observe that the Raman active B3g (3) out of phase scissor mode (SM) disappears above the dielectric transition temperature ( T c ) commensurate with the local structural distortions. DFT calculations show that the transformation of a room temperature Y-cation distorted orthorhombic structure to a perfect orthorhombic structure above the dielectric transition temperature in which the Y cation is undisplaced could lead to the conversion of SM with symmetry B3g to Raman inactive B1u mode.